UTILIZATION OF MEDIA NATURAL MATERIAL TO DEVELOP NATURALIS INTELLIGENCE OF CHILDREN AGE 5-6 YEARS - Uswatun Khasanah (Universitas Nahdlatul Ulama Lampung, 2015)
This study aims to determine the process of developing naturalist intelligence by utilizing the media of natural materials in children aged 5-6 years. The method used in this study uses John Elliot's action research method which has six steps: 1) identification of themes, 2) reconnaissance or review, 3) planning, 4) action, 5) observation or data collection, and 6) reflection. The data collected comes from field notes, interviews, documentation, and observation or observation. Data analysis using qualitative and quantitative descriptions. The results of this study indicate that the medium of natural materials can develop naturalist intelligence in children aged 5-6 years. Utilization of natural material media to develop naturalist intelligence includes children's knowledge of the natural environment, sensitivity to natural phenomena, environmental sustainability, caring for pets and plants. The naturalist intelligence of children aged 5-6 years develops well and increases through the medium of natural materials used.